Determinants Of Women’s Motivation As UMKM Actors In Improving The Family Economy In Medan City - Muhammad Indra Pratama; Isnaini Harahap; Budi Dharma (Dinasti Publisher, 2024)
The research aims to determine the determinants that influence women's motivation to become UMKM actors in improving the family economy in Medan City. This research uses quantitative methods with data collection techniques collected through questionnaires from research samples selected based on probability sampling techniques and determining 50 female respondents who are active as UMKM actors. Data analysis was carried out using descriptive statistical methods and multiple linear regression. The research results prove that economic factors, social factors and psychological factors explain 74.0% of UMKM motivation while the remaining 26.0% is explained by other factors outside the research.